2005
DOI: 10.1103/physrevlett.94.036106
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Distortions and Chemical Bonding of a Largeπ-Conjugated Molecule on a Metal Surface

Abstract: Normal incidence x-ray standing wave experiments and density functional theory reveal that 3,4,9,10-perylene-tetracarboxylic-dianhydride chemisorbs on Ag(111) in a nonplanar but vertically distorted configuration. The carboxylic O atoms are 0.18 +/- 0.03 angstroms closer to the surface than the perylene core. The distortion is related to weak, local bonds between carboxylic O atoms and the Ag surface which are coupled--through charge transfer into the former lowest unoccupied molecular orbital--to the primary,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(146 citation statements)
references
References 16 publications
9
135
1
Order By: Relevance
“…Hence, the metal is approximated with a finite number of metallic layers and a vacuum gap is inserted between the periodic images to decouple them. We used three metallic layers to perform the structural optimization of the systems in-line with previous investigations [10], [13]- [15], [17]- [19]. In all cases, the size of the unit cell along the surface normal was chosen to be 26 Å, which guarantees a sufficiently large vacuum gap (between 16 and 25 Å) for all studied systems.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, the metal is approximated with a finite number of metallic layers and a vacuum gap is inserted between the periodic images to decouple them. We used three metallic layers to perform the structural optimization of the systems in-line with previous investigations [10], [13]- [15], [17]- [19]. In all cases, the size of the unit cell along the surface normal was chosen to be 26 Å, which guarantees a sufficiently large vacuum gap (between 16 and 25 Å) for all studied systems.…”
Section: Methodsmentioning
confidence: 99%
“…Studies employing the generalized gradient approximation (GGA) [10], [13]- [15] reported adsorption distances much larger than the ones observed in experiment together with unrealistically small adsorption energies. In [16], the authors found better agreement with experiment, however, in connection with a strong arching of the molecule.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, the application of the GW approximation to finite systems was rather infrequent [10,11,12,13]. But there has been much recent increase in interest [14,15,16,17,18,19,20,21,22,23] in the application of the GW approximation to problems involving atoms, molecules, and clusters, in part driven by the quest to develop efficient techniques to address mixed systems such as molecular junctions [24,25,26,27,28].…”
Section: General Presentationmentioning
confidence: 99%